2016
DOI: 10.1093/cid/ciw236
|View full text |Cite
|
Sign up to set email alerts
|

Nonnucleoside Reverse-transcriptase Inhibitor- vs Ritonavir-boosted Protease Inhibitor–based Regimens for Initial Treatment of HIV Infection: A Systematic Review and Metaanalysis of Randomized Trials

Abstract: We found no difference in clinical and viro-immunologic outcomes between NNRTI- and PI/r-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
1
6
1
1
Order By: Relevance
“…A recent comprehensive metaanalysis found no difference in clinical or viro-immunological outcomes between NNRTIs and PIs but did not address resistance development. 10 Genotype analysis in our study of samples from patients failing treatment revealed NNRTI or NRTI resistance mutations in nearly three of four patients in the NNRTI-arm, which is even higher than that reported in other studies, 12,29 and reflect poor adherence. The high proportion of pre-therapy resistance can be due to transmitted resistance or previous ART exposure.…”
Section: A C C E P T E Dcontrasting
confidence: 68%
See 1 more Smart Citation
“…A recent comprehensive metaanalysis found no difference in clinical or viro-immunological outcomes between NNRTIs and PIs but did not address resistance development. 10 Genotype analysis in our study of samples from patients failing treatment revealed NNRTI or NRTI resistance mutations in nearly three of four patients in the NNRTI-arm, which is even higher than that reported in other studies, 12,29 and reflect poor adherence. The high proportion of pre-therapy resistance can be due to transmitted resistance or previous ART exposure.…”
Section: A C C E P T E Dcontrasting
confidence: 68%
“…This problem is even more pronounced in Black Africans, who more frequently harbour a polymorphism in cytochrome P450 2B6 associated with slower plasma clearance of efavirenz (EFV). 4 Large randomised trials comparing NNRTIs with protease inhibitors (PIs) have been conducted in Europe and the United States of America, [5][6][7][8][9][10] but these results are not generalisable to an African setting due to differences in genetics, sex distribution, and adherence. 4,11 Most studies comparing NNRTIs with PIs in adults that have been conducted in Africa have indicated equivalent efficacy; however, most of these studies only included women and treatment procedures were supported economically and practically to a larger extend than is common in the vast majority of centers in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Since its initial approval in 2006, substantial clinical trial data and clinical experience with darunavir have accumulated, demonstrating the potent and durable virologic response, high genetic barrier to resistance, and favorable safety profile in ART-naive, HIV-1-infected patients [ 4 , 5 ]. A substantial proportion of newly diagnosed patients in the United States and Europe are treated with a boosted protease inhibitor [ 6 , 7 ], and darunavir is the recommended protease inhibitor in treatment guidelines [ 8 – 10 ]. United States guidelines recommend two nucleoside or nucleotide analogue reverse transcriptase inhibitors (NRTIs) combined with an integrase strand transfer inhibitor (INSTI), or in certain clinical situations boosted darunavir 800 mg once daily or a nonnucleoside reverse transcriptase inhibitor (NNRTI) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…While a recent meta-analysis did not find differences between NNRTI- and PI/r-based regimens in terms of clinical outcomes such as death or progression to AIDS, it was found that trial-defined virological failure was higher with a NNRTI-based regimen [6]. Also, toxicity of certain NNRTIs were found to be inferior to PI/r-based regimen [7].…”
Section: Introductionmentioning
confidence: 99%